In vitro hair growth-promoting effects of araliadiol via the p38/PPAR-γ signaling pathway in human hair follicle stem cells and dermal papilla cells - Park, Seokmuk; Park, Han Woong; Seo, Dae Bang; Yoo, Dae Sung; Bae, Seunghee (Frontiers in Pharmacology, 2024)
Background: Scalp hair plays a crucial role in social communication by expressing personal appearance and self-identity. Consequently, hair loss often leads to a perception of unattractiveness, negatively impacting an individual's life and mental health. Currently, the use of Food and Drug Administration (FDA)-approved drugs for hair loss is associated with several side effects, highlighting the need for identifying new drug candidates, such as plant-derived phytochemicals, to overcome these issues.Objective: This study investigated the hair growth-promoting effects of araliadiol, a polyacetylene compound found in plants such as Centella asiatica.Methods: We employed an in vitro model comprising human hair follicle stem cells (HHFSCs) and human dermal papilla cells (HDPCs) to evaluate the hair growth-promoting effects of araliadiol. The proliferation-stimulating effects of araliadiol were assessed using water-soluble tetrazolium salt assay, adenosine triphosphate content assay, and crystal violet staining assay. In addition, we performed luciferase reporter assay, polymerase chain reaction analysis, cell fractionation, western blot analysis, and enzyme-linked immunosorbent assay (ELISA) to elucidate the mechanism underlying the hair growth-inductive effects of araliadiol.Results: Araliadiol exhibited both proliferation-and hair growth-promoting effects in HHFSCs and HDPCs. Specifically, it increased the protein expression of cyclin B1 and Ki67. In HHFSCs, it elevated the expression of hair growth-promoting factors, including CD34, vascular endothelial growth factor (VEGF), and angiopoietin-like 4. Similarly, araliadiol increased the expression of hair growth-inductive proteins such as fibroblast growth factor 7, VEGF, noggin, and insulin-like growth factor 1 in HDPCs. Subsequent western blot analysis and ELISA using inhibitors such as GW9662 and SB202190 confirmed that these hair growth-promoting effects were dependent on the p38/PPAR-γ signaling in both HHFSCs and HDPCs. Conclusion: Araliadiol promotes hair growth through the p38/PPAR-γ signaling pathway in human hair follicle cells. Therefore, araliadiol can be considered a novel drug candidate for the treatment of alopecia.